Polygamy in The Qur'an: An Integration of Classical Interpretation and Modern Linguistic Analysis - Moch. Iqbal; Ahmad Fihri; Fitri Zakiyah; Muhammad Choirin; Hashim Hassan Hashim Osman (Indonesian Journal of Arabic Studies, 2025)
Purpose: Studies on the theme of polygamy in Surah An-Nisa’ verses 3 and 129 have mostly been conducted from legal and social perspectives, while linguistic analysis of the verse’s linguistic structure—which is crucial for its meaning—is still rare. Therefore, this study places the discussion within the framework of Arabic linguistics and Qur’anic semantics by re-examining the function of one of the theories in Nahwu, namely ism maushūl, the syntactic structure, and the pragmatic implications of the verse. Methods: This study employs a descriptive-analytical literature review method to identify the main syntactic elements, examine semantic relations, and interpret the meaning of the text in the verse, drawing on classical and modern Arabic linguistic theories. Findings: The results show that the use of ism maushūl  "mā" in the verse on polygamy does not refer to women personally, but rather to certain social conditions that form the basis for the permissibility of polygamy. When examined linguistically, the verse emphasizes the existence of a “fair” condition that is pragmatically almost impossible to fulfill, so that polygamy is understood as an exception, not a recommendation. Research Implications: These findings demonstrate the importance of a linguistic approach in understanding legal verses and correcting common misconceptions about polygamy. This research also fills a gap in the study of Qur'anic linguistics.